KONSENTRASI ASAM ASETAT MEMENGARUHI KARAKTERISTIK FISIKOKIMIA PATI SAGU IHUR TERASETILASI - Febby J. Polnaya; Hilda Hilda; Cynthia G. C. Lopulalan (Jurnal Teknologi dan Industri Pangan, 2020)
Native ihur sago starch is a starch from Maluku and to date there is no report on its physicochemical properties. The objective of this work was to evaluate the effect of acetic acid concentration on the physicochemical properties of the native ihur sago starch. The starch was acetylated at different acetic acid concentrations, i.e., 0, 0.5, 1.5, and 2.5%. The acetylation was carried out by reacting ihur sago starch solution (100 g in 225 mL water) with acetic acid under alkaline condition. The acetyl group, degree of substitution (DS), water solubility, swelling power, paste clarity, and water, ash and amylose contents of the acetylated starch were measured. The study was conducted in three replications of non-factorial experiments using a completely randomized design. Starch modification through acetic acid addition produced ihur sago starch with different physicochemical characteristics from that of its native form. The acetylation caused the hydroxyl group in the starch to be substituted by acetyl group at concentration of 1.336-1.850% and DS range of 0.026-0.046, whilst no acetyl group was detected in its native starch. Acetylation increased the starch ash content from 0.46% to 0.50-0.57%, amylose content from 28.86% to 29.73-31.46%, solubility from 12.83% to 14.20-25.20%, swelling power from 18.51 g/g to 16.74-28.24 g/g and paste clarity from 93.07%T650 to 93.50-94.13%T650. In addition, acetylation at 0.5% increased the water content of the starch while higher concentration of acetylation could decrease its water content.